Rotavirus gastroenteritis complicating meningitis caused by Bacteroides uniformis detected using mNGS: a case report and literature review - Cai, Ze-zheng; Zeng, Dong-mei; Lei, Lu-wen; Xiao, Sa (Frontiers in Medicine, 2025)
This case report describes a rare instance of pediatric meningitis caused by Bacteroides uniformis (B. uniformis) following rotavirus gastroenteritis in a 1-year-4-month-old boy, diagnosed using metagenomics next-generation sequencing (mNGS). Bacterial meningitis (BM) is a life-threatening disease in children, particularly those under 5 years old, and early identification of the pathogen is crucial for reducing mortality and improving prognosis. B. uniformis, a Gram-negative, non-spore-forming, obligate anaerobic bacillus and common gut commensal, is rarely implicated in human infections, particularly pediatric meningitis. The child presented with vomiting, diarrhea, convulsions, and syncope, and was initially treated for meningitis and rotavirus gastroenteritis. Despite negative bacterial cultures, mNGS identified B. uniformis in the cerebrospinal fluid (CSF). Treatment was switched from ceftriaxone to meropenem (0.45 g, IV every 8 h) based on its good blood–brain barrier penetration and likely susceptibility of B. uniformis. The child’s condition improved significantly, with follow-up lumbar puncture showing normal CSF parameters and no detectable pathogens. The case suggests that rare anaerobic meningitis may occur against the backdrop of rotavirus gastroenteritis and underscores the importance of using mNGS for accurate pathogen detection in bacterial meningitis, as well as the need for early initiation of appropriate antimicrobial therapy.